2022
DOI: 10.1038/s41598-022-13397-6
|View full text |Cite
|
Sign up to set email alerts
|

Plasma taurine is an axonal excitability-translatable biomarker for amyotrophic lateral sclerosis

Abstract: Although various body fluid biomarkers for amyotrophic lateral sclerosis (ALS) have been reported, no biomarkers specifically reflecting abnormalities in axonal excitability indices have currently been established. Capillary electrophoresis time-of-flight mass spectrometry and liquid chromatography time-of-flight mass spectrometry were used to perform a comprehensive metabolome analysis of plasma from seven ALS patients and 20 controls, and correlation analysis with disease phenotypes was then performed in 22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…A major issue with most of the studies is a discordance in collection protocols and how each is related to the clinical stage of disease, including time from diagnosis, and relationship to ALSFRS-R. 222 Meta-analysis including CSF and serum showed 16 pathways altered in ALS, 221 including caffeine metabolism, aminoacyl-tRNA biosynthesis and valine, leucine and isoleucine biosynthesis. However, it is not clear in the metabolomics studies if the samples were all taken from ALS patients with similar ALSFRS-R and time from diagnosis.…”
Section: Urinary Metabolomementioning
confidence: 99%
“…A major issue with most of the studies is a discordance in collection protocols and how each is related to the clinical stage of disease, including time from diagnosis, and relationship to ALSFRS-R. 222 Meta-analysis including CSF and serum showed 16 pathways altered in ALS, 221 including caffeine metabolism, aminoacyl-tRNA biosynthesis and valine, leucine and isoleucine biosynthesis. However, it is not clear in the metabolomics studies if the samples were all taken from ALS patients with similar ALSFRS-R and time from diagnosis.…”
Section: Urinary Metabolomementioning
confidence: 99%
“…TUDCA activates GpBAR1, and inhibits the pro-inflammatory NFκB pathway in microglia, resulting in the inactivation of proinflammatory status in multiple sclerosis (MS) ( Bhargava et al, 2020 ). Despite a lack of consensus if BA disturbance is a response toward developing neuropathology or the initial cause of the neuropathology observed ( Dodge et al, 2021 ), the alteration of BAs content in the plasma can serve as an early diagnostic biomarker for AD ( Shao et al, 2020 ), PD ( Graham et al, 2018 ), MS ( Bhargava et al, 2020 ), and amyotrophic lateral sclerosis (ALS) ( Nakazato et al, 2022 ).…”
Section: Contribution Of Bile Acid and Its Signaling Components To Ne...mentioning
confidence: 99%
“…Taurine values have also been examined in biological samples such as blood and cerebrospinal fluid (CSF). A recent study found that taurine plasma levels correlated with the strength-duration time constant, an axonal excitability indicator, established to predict survival in amyotrophic lateral sclerosis (ALS) ( Nakazato et al, 2022 ). Furthermore, taurine was selected as a biomarker metabolite that helps to distinguish between patients with amnestic mild cognitive impairment and healthy controls ( Sun et al, 2020 ).…”
Section: Taurine As a Therapeutic Alternative In Nervous System Patho...mentioning
confidence: 99%